2015
DOI: 10.1200/jco.2014.58.3708
|View full text |Cite
|
Sign up to set email alerts
|

Overall Survival and Long-Term Safety of Nivolumab (Anti–Programmed Death 1 Antibody, BMS-936558, ONO-4538) in Patients With Previously Treated Advanced Non–Small-Cell Lung Cancer

Abstract: Nivolumab monotherapy produced durable responses and encouraging survival rates in patients with heavily pretreated NSCLC. Randomized clinical trials with nivolumab in advanced NSCLC are ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
821
1
16

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,054 publications
(863 citation statements)
references
References 38 publications
(10 reference statements)
25
821
1
16
Order By: Relevance
“…In tissue biopsies, expression of the biomarker PD-L1 alone is not a prognostic indicator of survival in lung cancer, while RAD50 foci formation has been indicated as positively correlated with survival (14,18,20,24,29,30,32,35,39,40,42). We analyzed the clinical outcomes of patients based on expression of PD-L1, or the average number of RAD50, at both T0 and T1 time points (Fig.…”
Section: Pd-l1 and Rad50 In Circulating Cells As Potential Prognosticmentioning
confidence: 99%
See 1 more Smart Citation
“…In tissue biopsies, expression of the biomarker PD-L1 alone is not a prognostic indicator of survival in lung cancer, while RAD50 foci formation has been indicated as positively correlated with survival (14,18,20,24,29,30,32,35,39,40,42). We analyzed the clinical outcomes of patients based on expression of PD-L1, or the average number of RAD50, at both T0 and T1 time points (Fig.…”
Section: Pd-l1 and Rad50 In Circulating Cells As Potential Prognosticmentioning
confidence: 99%
“…PD-L1/PD-1 immune blockade drugs (e.g., nivolumab and pembrolizumab) are potent immune checkpoint inhibitors that have been shown to dramatically shrink and stabilize tumors in approximately 20% of patients with NSCLCs (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). These types of immunotargeted therapeutics specifically alter a patient's stromal interactions by activating the host's immune cell response against the presence of tumor cells (29-36, 41, 42).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term survival and delayed clinical effect observed in multiple cancer immunotherapy phase III clinical trials with timeto-event endpoints (5,6,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) pose unique statistical challenges in study design. Four basic models summarize how the long-term survival and delayed clinical effects affect the study design with time-to-event endpoints (41).…”
Section: Impact Of Survival Kinetics On Study Designmentioning
confidence: 99%
“…11, 12) and the PD-1 ligand, PD-L1 (13), led to the selection of "Cancer Immunotherapy" as the 2013 Breakthrough of the Year by Science (14). Nivolumab, a fully human IgG4 (Immunoglobulin G subclass 4) monoclonal antibody to PD-1, showed promising efficacy in multiple tumor types (15)(16)(17)(18). The significant survival benefit led to decisions by data monitoring committees to discontinue ahead of schedule four randomized phase III nivolumab clinical trials in metastatic melanoma (19), squamous and nonsquamous non-small cell lung cancer (NSCLC; refs.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have also suggested that clinical response rates strongly correlate with PD-L1 expression status. This was first demonstrated in a phase I study of nivolumab in solid tumors (CA209-003) 24 . Of 46 patients with melanoma, NSCLC, or RCC, 25 tumors were positive and 21 were negative for PD-L1.…”
mentioning
confidence: 92%